2021
DOI: 10.1021/acsapm.1c00681
|View full text |Cite
|
Sign up to set email alerts
|

A Creative Approach to Prepare a Macromolecular Flame Retardant with Flexibility: DOPO-Modified Epoxidized Polybutadiene

Abstract: The incorporation of large loading of flame retardants generally causes embrittlement of materials. However, most of the rubbers and thermoplastic elastomers are flammable. Therefore, preparation of a flame retardant with potential toughening characteristics is urgently required for preparing materials with both good flame retardancy and toughness. The objective of the present work was to prepare a macromolecular flame retardant with good flexibility, that is, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Studies have shown that incorporating DOPO into RPUF can even improve mechanical properties. Qin 9 developed a macromolecular DOPO‐based flame retardant EPB‐DOPO with good flexibility. In addition to showing good thermal stability, it also had excellent compression elasticity after ignition.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that incorporating DOPO into RPUF can even improve mechanical properties. Qin 9 developed a macromolecular DOPO‐based flame retardant EPB‐DOPO with good flexibility. In addition to showing good thermal stability, it also had excellent compression elasticity after ignition.…”
Section: Introductionmentioning
confidence: 99%